(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Women empowerment and the movement towards gender equality is a modern phenomenon that continues to develop around the world. To be precise, women empowerment refers to a process of empowering women with all the denied aspects of life. Reforms undertaken in the early 1990s have made India one of the world’s fastest growing economies. However, it is interesting to note that this economic growth had bypassed the poor and vulnerable, especially, women.People in low-power positions, whether due to gender or class, tend to exhibit other-oriented rather than self-oriented behavior. Women’s experiences at work and at home are shaped by social class, heightening identification with gender for relatively upper class women and identification with class for relatively lower class women, potentially mitigating, or even reversing, class-based differences documented in past research. Gender–class differences are reflected in women’s employment beliefs and behaviors. Research integrating social class with gendered experiences in homes and workplaces deepens our understanding of the complex interplay between sources of power and status in society.